Omega–Phi compensated GID in side inclination mode for measurement of residual stress in polycrystalline thin films. (30th January 2018) - Wang, Xiaodong; van Riessen, Arie
Abstract : The grazing incidence diffraction (GID) method in side inclination mode, described by Ma et al . in 2002, of polycrystalline thin-film residual stress was revisited and explained using simple geometric relations. To overcome the issue of decreasing peak intensity of this method, which is induced by the decreasing incident angle because of the Eulerian cradle Chi-tilt, an improvement of Omega ( ω )–Phi ( φ ) compensation was devised and applied to a NiFe thin-film sample. The geometry of this improved ω – φ compensated GID method in side inclination mode is detailed in this paper. This improvement guarantees a constant incident angle on the sample surface and a fixed sample illumination volume during measurement. The measured data were analysed using parametric refinement in DIFFRAC.TOPAS v6 software in Launch Mode, and details of the input file (.INP) are explained in this paper. The tensile stress of the NiFe thin-film sample was measured to be 1181 ± 85 MPa using this improved method.